Vegetative hemostasis under influence of rehabilitation therapy in children with cervicogenic headache - N. V. Korolenko; O. V. Gorsha (Kazimierz Wielki University, 2017)
The purpose of research was studying clinical effect of separate and combined application of kinesio taping and physical therapy exercises and their influence on the state of the vegetative regulation of cardiac rhythm in children of young school age with the cervicogenic headache against a background of cervical spine instability. The materials for the research were the results of examination of 96 children of younger school age having cervicogenic headache longer whan 6 months (the basic group), and 30 healthy children of the same age (the control group). Combined application of kinesio taping and the physical therapy exercises complex much better improves the clinical state of the patients (than usage of the these methods separately) both immediately after the treatment (86.6%) and in 6 months - the headache does not reoccure in the most of children (61.5%). The achieved values after the combined application of methods of both statistical and spectral indices of heart rhythm variability were better as comparied with separate application of the researched methods of restoration treatment. The combined application of kinesio taping and physical therapy exercises leads to the most pronounced optimization of the Bayevskyy tension index value immediately after the treatment and in predominance of eutonia in case of reduction of vagotonic vegetative tone in all points of research, as well as increase of favourable sympathicotonic character of vegetative reactivity with reduction of hypersympathicotonic type, which proves the improvement of the vegetative regulation of heart rhythm in children with cervicogenic headache against a background cervical spine instability.